Reposisi Peran Guru PAI di Era Artificial Intelligence: Pendidik, Motivator, dan Inovator dalam Pembelajaran - Ma’arif Abdul Karim Islam (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2026)
The development of Artificial Intelligence (AI) is transforming the learning ecosystem and reshaping teachers' roles, including those of Islamic Religious Education (PAI) teachers. This study aims to analyze and synthesize the repositioning of PAI teachers’ roles in learning in the AI era. The study employs a qualitative approach using a library research method. Relevant literature was identified through searches of Google Scholar, Scopus, and Garuda using keywords related to AI in education, Islamic education, PAI teachers, and digital learning. The selected literature was analyzed using qualitative content analysis through the stages of identification, selection, information extraction, coding, categorization, and thematic synthesis. The findings indicate that AI has the potential to expand access to information, support personalization, enhance interactivity, and create opportunities for learning innovation. However, in the context of PAI, the use of AI needs to be directed toward educational goals that encompass knowledge, morality, adab, and spiritual awareness. The literature synthesis positions PAI teachers within three interconnected functions: educator as a guide to knowledge and values and a cultivator of students’ moral character; motivator as a facilitator of meaningful learning engagement and motivation; and innovator as a designer of creative, critical, ethical, and value-based digital learning. This study develops a conceptual understanding of AI as a wasilah or means of learning, while the teacher serves as a mediator between the potential of technology and the goals of Islamic education. The findings imply that the development of PAI teachers’ competencies needs to integrate AI and digital literacy, digital pedagogy, mastery of PAI content, information curation skills, and ethical and Islamic value literacy, supported by an adequate learning ecosystem.